Reforming democracy: Comment on "Proposals for a Democracy of the Future"by Bruno Frey - Hannu Nurmi (Springer Verlag, 2022)
Of Frey’s ideas about expanding the scope of direct democracy we focus on the problems related to agenda formation, graded votes, random devices in elections and the majority principle. Hopefully these points will be addressed in further development of those ideas.